Comparison of Mean Vitamin B12 Levels Among Patients with Mild To Moderate and Severe Depression, Using Hamilton Depression Rating Scal - Sharif, Assam Muhammad Bin; Ali, Sohail; Shabbir, Ayesha; Pervez, Zoonash Zara; Khan, Maria Ahmed; Gohar, Razi Ur Rehman (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess vitamin B12 deficiency and compare mean levels among patients with mild to moderate, and severe depression, using Hamilton Depression Rating Scale.Study Design: Analytical cross-sectional study.Place and Duration of Study: Armed Forces Institute of Mental Health (AFIMH), Rawalpindi, Pakistan, from Aug to Mar 2021.Methodology: A total of 260 patients with diagnosed clinical depression with intensity ranging from mild to moderate, and severe, as per Hamilton Depression Rating (HAM-D) Scale, were included in this study. Patients were enrolled from the Outpatient Department of AFIMH and Depression Severity Scores (HAM-D score) and serum vitamin B12 levels were recorded for all participants.Results: The average age of participants was 42.37±12.55 years. There were 105(40.38%) male and 155(59.62%) female patients. Out of 260 patients with depression, 185(71.15%) had mild to moderate depression and 75(28.85%) had severe depression. Frequency of vitamin B12 deficiency among patients with depression was 186(71.54%) while mean vitamin B12 levels were significantly higher in patients with severe depression as compared to patients with mild to moderate depression [245.53±63.98 vs. 173.39±51.97; p=0.0005].Conclusion: We found that patients with depressive disorders commonly have vitamin B12 deficiencies correlating with mild to moderate depressive symptoms.